Glycaemic responses in Asian and non-Asian people with type 2 diabetes initiating insulin glargine 100 units/mL: A patient-level pooled analysis of 16 randomised controlled trials - Juliana C.N. Chan (2019)
© 2017 Aims To compare outcomes between Asian and non-Asian patients with type 2 diabetes (T2D) inadequately controlled on oral antidiabetic drugs (OADs) initiating insulin glargine 100 units (U)/mL (Gla-100) in randomised controlled clinical trials. Methods Post hoc analysis of patient-level data (Asian n = 235; non-Asian n = 3351) from 16 trials. Results At baseline, Asian patients were younger with lower body mass index (BMI), fasting C-peptide, and fasting plasma glucose (FPG) than non-Asian patients (all P <.001). Asian patients had a higher mean glycosylated haemoglobin (HbA1c) at Week 24 and less reduction in HbA1c from baseline (7.4% vs. 7.2%; −1.3% vs. −1.6%, respectively; P =.0001), and were less likely to achieve HbA1c <7.0% (40% vs. 47%; P =.002) than non-Asian patients. Reductions in FPG and rates of hypoglycaemia were similar between Asian and non-Asian patients. Asian patients had less weight gain than non-Asian patients (+1.3 vs. +1.9 kg, respectively, P =.013). Conclusions In our post hoc meta-analysis, Gla-100 effectively lowers HbA1c and FPG in Asian patients with T2D uncontrolled on OADs with similar incidence of hypoglycaemia and less absolute weight gain compared with non-Asian patients. At a similar FPG reduction, fewer Asian patients achieved HbA1c target <7.0%, suggesting that prandial glucose needs to be addressed.